Sensorless Position Control and Speed Estimation Techniques of Permanent Magnet Synchronous Motors - Musa Lawan; Ibrahim Tijjani; Musa Mustapha; Musa Aliyu Sarki (Peneliti Teknologi Teknik Indonesia, 2023)
This research article presents a review regarding the various techniques used for sensorless position and speed of estimation of permanent magnet synchronous motor drives. Permanent-magnet synchronous machines (PMSMs) are widely used in high performance applications because of their compact size, high-power density, high efficiency, free maintenance etc. Mechanical sensors are normally required for speed control of PMSM in sensing rotor position and speed to achieve drive system. However, these sensors increases the overall system cost, size, weight, and wiring complexity thereby reducing the mechanical robustness and the reliability of the overall PMSM drive systems. Sensorless drives are becoming more and more important as they can eliminate speed sensors maintaining accurate response; hence sensoreless methods have gained much attention. This paper presents different sensorless position and speed estimation techniques of PMSM motor drives system and their corresponding advantages and disadvantages are described.